Гендерний вимір жаргонної лексики в ідіостилі письменника (на матеріалі романів Ірени Карпи «Добло і зло» та Сергія Жадана «Депеш Мод») - Лиманська, Анна Сергіївна; Lymanska, A. S. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Робота присвячена дослідженню гендерного жаргонної виміру лексики в ідіостилі Ірени Карпи й Сергія Жадана. Об’єкт дослідження – жаргонна і сленгова лексика в ідіостилі Ірени Карпи й Сергія Жадана. Предметом вивчення є структурно-семантичні особливості мовних одиниць сленгової лексики, що наявні в романах «Добло і зло» й «Депеш Мод», прояви фемінного й маскулінного в обарній групі мовних одиниць. У кваліфікаційній роботі зроблено спробу дослідити специфіку ідіостилю С. Жадана й І. Карпи, проаналізувати тематичні групи сленгу, окреслити гендерний вимір жаргонної лексики на матеріалі текстів романів «Добло і зло» й «Депеш Мод». Поняття «сленг», «жаргон», «гендер» описано за довідковими, підручниковими й монографічними джерелами. Окреслено функції сленгової лексики в мові художньої літератури, її роль у формуванні ідіостилю письменника.

The thesis focuses on the study of gender-specific dimension of slang lexicon in the idiolect of Irena Karpa and Serhiy Zhadan. The subject under investigation is the the slang and colloguial lexicon in the idiolect of Irena Karpa and Serhiy Zhadan. The object of the study is the structural and semantic features of linguistic units of slang lexicon present in the novels "Good and Evil" and "Depeche Mode," manifestations of feminine and masculine in the lexical group of language units. In the qualifying work, an attempt was made to explore the specificity of the idiolect of S. Zhadan and I. Karpa, analyze thematic groups of slang, outline the gender dimension of slang lexicon based on the material of the texts of the novels "Good and Evil" and "Depeche Mode." The concepts of "slang," "jargon," and "gender" are described using reference, textbook, and monographic sources. The functions of slang lexicon in the language of fiction literature and its role in the formation of the writer's idiolect are outlined.
Gender Dimension of Slang Lexicon in the Idiolect of the Writer (Based on the Novels "Good and Evil" by Irena Karpa and "Depeche Mode" by Serhiy Zhadan)
Keywords: сленг; жаргон; гендер; фемінне; маскулінне; Сергій Вікторович Жадан (1974 - ); Ірена Ігорівна Карпа (1980 - ); сучасна література; slang; jargon; gender; feminine; masculine; Serhiy Zhadan (1974 - ); Irena Karpa (1980 - ); HUMANITIES and RELIGION::Aesthetic subjects::Literature